Lady Daisy - King-Smith, Dick.; Littlewood, Valerie (London : Puffin, 1993)
Nine-year-old Ned finds a doll in his grandmother's attic, and to his surprise, she talks. Lady Daisy Chain tells him about life in Victorian times.
6.5
3-6
Keywords: Dolls -- Fiction; Imagination -- Fiction; Dolls -- Fiction; Imagination -- Fiction; England -- Fiction; England -- Fiction